A120 PEDIATRIC TO ADULT TRANSITION OF CARE IN IBD: ESTABLISHING THE CURRENT STANDARD OF CARE AMONGST CANADIAN ADULT ACADEMIC GASTROENTEROLOGISTS - Jawaid, N (J Can Assoc Gastroenterol, 2018)
BACKGROUND: Current consensus on pediatric to adult IBD transition is influenced primarily by pediatric gastroenterologists. While transition extends to age 25, there has not been a systematic effort to define current standard of care amongst adult gastroenterologists providing IBD transition care. AIMS: The purpose of this study was to establish current transition practices across Canada amongst adult gastroenterologists in high volume GI centers. METHODS: Within Canada, only 8 provinces have large pediatric centers, thought to care for the majority of pediatric onset IBD. There are 14 adult GI academic centers across Canada, thought to receive the majority of pediatric to adult IBD transfers of care. Adult gastroenterologists with an interest in pediatric to adult IBD transition were identified through research and clinical networks. A total of 10 semi-structured interviews representing 8 adult GI centers across 6 provinces were conducted to reflect practice patterns at the highest volume transition centers across Canada. Questions focused on the transition process – referral practices, information transfer and access to multidisciplinary resources. Subjective assessments were identified as well as transition-related quality indicators. The interviews were audio-recorded, transcribed and coded for qualitative thematic analysis. RESULTS: Transition practices were divided into a transition clinic (n=3) vs. direct transfer to an adult gastroenterologist (n=5). The majority of transition patients were referred to academic centers with the notable exception of British Columbia. The volume of transferring patients ranged from 12 to 100 per year, most averaged 30–40 patients/year. Transfer of information was optimized with a pediatric-adult electronic medical record system. Only one program did not have access to an IBD nurse but the majority lacked consistent access to a multidisciplinary team. Strongest attributes related to healthcare providers interested in transition and meaningful transfer of information from pediatrics. Major areas for improvement included increased resource allocation. All participants agreed that a consensus-based guideline standardizing adult-phase transfer and transition would be beneficial. Potential quality indicators included adherence, wait time, depression/anxiety scores and patient education. CONCLUSIONS: This Canadian survey of adult gastroenterologists representing high volume adult IBD transition centers reveals that practice patterns vary but ideally involve a dedicated transition clinic with access to multi-disciplinary resources. A consensus-based guideline and quality indicators may assist in standardizing adult-phase transition and optimizing outcomes. FUNDING AGENCIES: None